Assistance and Transfer of Hajj Quota to Families and Heirs in Indonesia: The Perspective of Maqasid Bin Bayyah and Priority Fiqh Yusuf Qardhawi - Hidayat, Moh (Journal Social Civilecial, 2026)
The limited availability of Indonesia’s Hajj quota, combined with long waiting periods, creates legal and ethical questions concerning companion allocation for vulnerable pilgrims and the transfer of Hajj registration portion numbers to heirs. This study examines these mechanisms through the perspectives of Abdullah Bin Bayyah’s maqāṣid al-sharī‘ah and Yusuf al-Qaradawi’s fiqh al-awlawiyyāt. Using normative legal research, the study applies statutory, conceptual, Islamic jurisprudential, philosophical, and comparative-balancing approaches. Primary and secondary legal materials were collected through library and document research and analyzed qualitatively through legal interpretation, maqāṣid classification, priority assessment, and prescriptive evaluation. The findings show that companion allocation is justified when it is objectively necessary to protect religion, life, intellect, property, and human dignity, particularly where the absence of assistance would endanger the pilgrim or prevent the completion of the rites. However, accompaniment based merely on preference or convenience should not override the rights of long-waiting prospective pilgrims. The transfer of a deceased pilgrim’s registration portion number may protect deposited funds, administrative certainty, religious intention, and family interests, but the registration position cannot be treated as an absolute inheritable property right because it operates within a limited public quota system. Therefore, both mechanisms must be conditional, proportionate, transparent, and subject to objective eligibility criteria. The study recommends verified medical and functional assessments for companion allocation, clear limitations on transfers, protection of heirs’ financial rights, prohibition of commercialization, and continuous evaluation of the impact on the waiting list. Such measures reconcile humanitarian protection, administrative certainty, and distributive justice in Hajj governance.